Phemius Suite - Thomas, Oliver (Cambridge University Press, 2014)
This article examines four connected aspects of Phemius’ performance in Odyssey 1. The first section examines the poet’s unusual technique in relating Phemius’ music to other, simultaneous sounds in the ‘soundscape’ of Odysseus’ hall. The second argues that the suitors’ initial dancing develops into a theme of appropriate and inappropriate nimbleness which, in particular, creates significant connections between books 1 and 22. The third section shows that the poet is suggestive but studiedly vague on the politics of Phemius’ first song which, in the final section, I interpret as a self-reflexive and open-ended ‘lesson’ in how to read epic.